2023
DOI: 10.3892/or.2023.8647
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 accelerates cell proliferation, migration, and tumor growth by upregulating ZEB1/H4R3me2as in thyroid carcinoma

Guoli Feng,
Changju Chen,
Yi Luo

Abstract: Thyroid carcinoma (TC) represents the most prevalent malignancy of the endocrine system. Protein arginine methyltransferase 1 (PRMT1) is a critical member of the protein arginine methyltransferase family in mammals and is involved in multiple biological processes. This study aimed to investigate the function of PRMT1 in TC. In the present study, human TC cell lines (8505C, CAL62, and BCPAP) and a normal human thyroid cell line Nthy-ori 3-1 were employed. Small interfering RNA targeting PRMT1 was used to knock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…PRMT1, a type I enzyme, is the predominant isoform in mammalian cells accounting for ~85% of total protein arginine methylation (Tang et al, 2000 ). Knockout of PRMT1 in mice results in embryo lethality (Pawlak et al, 2000 ) while altered PRMT1 protein expression has been reported in various types of cancer, including lung, breast, bladder, and pancreatic cancers (Feng et al, 2023 ; Filipović et al, 2019 ; He et al, 2020 ; Song et al, 2020 ; Wang et al, 2019 ; Yoshimatsu et al, 2011 ), as well as in idiopathic pulmonary fibroses (Lambers et al, 2019 ; Zakrzewicz et al, 2014 ; Zakrzewicz et al, 2015 ) and asthma (Park et al, 2021 ; Sun et al, 2017 ). The catalytic core of PRMT1 contains a Rossman fold that binds the cofactor AdoMet, a beta‐barrel that is thought to be involved in substrate binding (Schapira & Ferreira de Freitas, 2014 ), and a dimerization arm.…”
Section: Introductionmentioning
confidence: 99%
“…PRMT1, a type I enzyme, is the predominant isoform in mammalian cells accounting for ~85% of total protein arginine methylation (Tang et al, 2000 ). Knockout of PRMT1 in mice results in embryo lethality (Pawlak et al, 2000 ) while altered PRMT1 protein expression has been reported in various types of cancer, including lung, breast, bladder, and pancreatic cancers (Feng et al, 2023 ; Filipović et al, 2019 ; He et al, 2020 ; Song et al, 2020 ; Wang et al, 2019 ; Yoshimatsu et al, 2011 ), as well as in idiopathic pulmonary fibroses (Lambers et al, 2019 ; Zakrzewicz et al, 2014 ; Zakrzewicz et al, 2015 ) and asthma (Park et al, 2021 ; Sun et al, 2017 ). The catalytic core of PRMT1 contains a Rossman fold that binds the cofactor AdoMet, a beta‐barrel that is thought to be involved in substrate binding (Schapira & Ferreira de Freitas, 2014 ), and a dimerization arm.…”
Section: Introductionmentioning
confidence: 99%